Microbiologic Diagnosis of Pyogenic Spondylitis - Kim, Nam Joong (Infect Chemother, 2021)
Pyogenic spondylitis requires long-term antibiotics treatment and identification of the etiologic microorganism is essential. The first test in the microbiologic diagnosis of pyogenic spondylitis is a blood culture. Any microorganisms that grow in blood culture are highly likely to be the etiological microorganisms of pyogenic spondylitis. If the microbial etiology cannot be defined by the blood culture, a needle biopsy is performed on the inflamed tissues. Here, it is recommended that paraspinal tissues, rather than spinal tissues, are collected to increase the positive rate in tissue culture. If the microbial etiology cannot be defined by the first needle biopsy, another needle biopsy may be performed. The collected tissue sample is used in culture tests on bacteria and mycobacteria as well as pathological tests. If tuberculous spondylitis is suspected, polymerase chain reaction is carried out to detect Mycobacterium tuberculosis. In the case that the etiological microorganisms cannot be identified, the data of the patient regarding age, sex, vertebrae involved, history of spinal surgery or procedure, previous or concurrent urinary tract or intra-abdominal infection are analyzed. Based on this the most probable microbial etiology is determined to select the antibiotics to be used in the empiric treatment.